A prospective study of the importance of enteric fever as a cause of non-malarial febrile illness in patients admitted to Chittagong Medical College Hospital, Bangladesh. - Maude, R; Ghose, A; Samad, R; de Jong, H; Fukushima, M; Wijedoru, L; Hassan, M; Hossain, M; Karim, M; Sayeed, A; van den Ende, S; Pal, S; et al. (BioMed Central, 2016)
Background Fever is a common cause of admission to hospital in Bangladesh but causative agents, other than malaria are, not routinely investigated; enteric fever is thought to be common. Methods Adults and children admitted to Chittagong Medical College Hospital with a temperature of ≥38.0oC were investigated in detail using a blood smear for malaria, a blood culture, real-time PCR to detect Salmonella Typhi, S. Paratyphi A and other pathogens in blood and CSF and NS1 anatigen dengue ELISA. Results We enrolled 300 patients with fever that were malaria smear negative between January and June 2012: 156 children (aged ≤15 years) and 144 adults with a median (interquartile range) age of 13 (5-31) years and median (IQR) duration of illness before admission of five (2-8) days. Clinical syndromes included: enteric fever in 52 patients (17.3%), lower respiratory tract infection in 48 patients (16.0%), non-specific febrile illness in 48 patients (16.0%), a CNS infection in 37 patients (12.3%), urinary sepsis in 23 patients (7.7%), an upper respiratory tract infection in 21 patients (7.0%), and diarrhea or dysentery in 21 patients (7.0%). Despite a negative microscopy malaria was still suspected in seven patients. S. Typhi was detected in blood by culture or PCR in 34/56 (65.4%) of patients in which typhoid was suspected. Rickettsia typhi and Orientia tsutsugamushi were detected by PCR in two and one patient respectively and two patients were dengue NS1 antigen positive. Twenty-nine (9%) patients died during their hospital admission: 15/160 (9.4%) of children and 14/144 (9.7%) adults; 2/56 (3.6%) patients with enteric fever, 5/48 (10.4%) patients with lower respiratory tract infections, and 12/36 (33.3%) patients with encephalitis/meningitis. Conclusion Enteric fever was responsible for nearly one in five admissions to this hospital in Chittagong, Bangladesh with non-malaria fever with the diagnosis confirmed in two thirds. Lower respiratory tract infections and CNS infections were also common. The etiology of CNS infections in this location merits more detailed study due to the high mortality rate.